Design and the question of history - Fry, Tony; Dilnot, Clive; Stewart, Susan C. (Susan Catherine Huston) (Design, history, futures, 2015)
"Design and the Question of History offers a new perspective on the historical significance of design, showing how design is an agent of historical change rather than a single aspect. Despite a historical sensibility being essential in making critical and directional choices, Design History presents an extremely selective view, which cannot deliver the historical knowledge to sufficiently and sensitively inform designers and design thinkers' practice. Focusing on how the relationship between design and history is understood and presented, this book uses a methodological approach to address this problem. The book covers the issue of history and how design in history needs to be understood by recognising that design is always historically embedded in a relational context; the efficacy of Design History as a sub-discipline within design; and the delivery of a more substantial historical sensibility to emergent designers, identifying the pedagogic problems it presents and discussing the agency of such knowledge in practice. This book is the flagship of the Design, History & Futures series, edited by Tony Fry, Lisa Norton and Anne-Marie Willis" -- Provided by publisher.